Control of magneto-transport characteristics of Co-doped ZnO by electron beam irradiation. Issue 47 (25th April 2016) - Lee, Seunghun; Park, Ji Hun; Kim, Won-Kyung; Park, Hyung Dal; Lee, Byung Cheol; Moriyoshi, Chikako; Kuroiwa, Yoshihiro; Lee, Geun Woo; Chan Cho, Yong; Jeong, Se-Young
Abstract : Electron beam irradiation can be used to remove shallow donor type hydrogen located in Zn(Co)–O bonding centers in Co-doped ZnO, which enables to modify the conduction band and the magneto-transport characteristics of Co-doped ZnO. Abstract : Electron beam irradiation can be used to modify the physical properties of materials, but its effects have never been studied in Co-doped ZnO (ZnCoO), a promising magnetic semiconductor material. Here, we demonstrate that electron beam irradiation enables modification of the magneto-transport properties of ZnCoO. The electron beam irradiation cannot affect the electrical and magnetic properties of ZnCoO significantly, due to the insulating nature of pristine ZnCoO showing paramagnetic behavior. However, intentional hydrogen doping increases carrier concentration and induces ferromagnetism in ZnCoO, which allows ZnCoO to be affected by electron beam irradiation. As a consequence of s–d exchange interaction, hydrogen-doped ZnCoO shows positive magnetoresistance and anomalous Hall conductivity. Electron beam irradiation reduced the carrier concentration in hydrogen-doped ZnCoO by removing shallow donor-type hydrogen and consequently increasing s–d exchange interaction, which resulted in an increase in positive magnetoresistance and a decrease in the anomalous Hall conductivity. These findings demonstrate the novel applicability of electron beam irradiation for tailoring the physical properties of ZnO-based materials.